Arab men who have sex with men in Israel: knowledge, attitudes and sexual practices. Issue 4 (7th September 2015) - Mor, Z; Grayeb, E; Beany, A
Abstract : Objectives: Arab men who have sex with men (AMSM) are becoming visible in society, and reports of HIV infection and sexually transmitted infections (STIs) are emerging. This study aimed to assess the knowledge of AMSM regarding HIV transmission, their attitudes towards condom use and their sexual practices compared with Jewish MSM (JMSM), and to evaluate AMSM–JMSM friendships and sexual encounters. Methods: Participants in this cross‐sectional study completed questionnaires in Arabic or Hebrew. The outcome variable was unprotected anal sex (UAI) in the previous 6 months with a partner(s) whose HIV status was discordant or unknown. AMSM and JMSM indicated if they had friends or sexual encounters from the other ethnic group. Results: The questionnaires were completed by 342 (16.2%) AMSM and 1775 (83.8%) JMSM in 2012. AMSM were more likely to be religious, 'closeted' and married than JMSM; their knowledge regarding HIV transmission was inferior and attitudes towards condom use were less favourable. AMSM reported less alcohol and drug use than JMSM, were more likely to be attracted to and have sex with women, and reported a greater number of sexual partners and more UAI. Being AMSM was a predictive variable for UAI in the multivariate model. While 178 AMSM (52.0%) reported that most of their close friends were JMSM, 251 (73.4%) had only/mostly sexual encounters with JMSM. Among JMSM, 41 (2.3%) reported that their close friends were AMSM, and 308 (17.3%) had only/mostly sexual encounters with AMSM. Conclusions: The knowledge of AMSM regarding HIV transmission and their attitudes towards condom use were less favourable than those of JMSM, and they performed more UAI. AMSM may benefit from targeted interventions, including reconciling their same‐sex attraction in positive terms. Same‐sex attraction and gay identity may provide common ground to strengthen Arab–Jew communication in Israel.